2018
DOI: 10.1029/2017wr021176
|View full text |Cite
|
Sign up to set email alerts
|

Development of Probabilistic Dam Breach Model Using Bayesian Inference

Abstract: Dam breach models are commonly used to predict outflow hydrographs of potentially failing dams and are key ingredients for evaluating flood risk. In this paper a new dam breach modeling framework is introduced that shall improve the reliability of hydrograph predictions of homogeneous earthen embankment dams. Striving for a small number of parameters, the simplified physics‐based model describes the processes of failing embankment dams by breach enlargement, driven by progressive surface erosion. Therein the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 69 publications
2
13
0
Order By: Relevance
“…Results are given in Figure 9 and Table S2 for different experimental designs. The PCE degree shown in the appendix is the PCE degree with the lowest LOO in the array of the given degrees (i.e., [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] [54]. The results showed that with the increasing ED the value of LOO decreases, and the degree of the calculated PCE changes as well.…”
Section: Step C Uncertainty Propagationmentioning
confidence: 99%
“…Results are given in Figure 9 and Table S2 for different experimental designs. The PCE degree shown in the appendix is the PCE degree with the lowest LOO in the array of the given degrees (i.e., [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] [54]. The results showed that with the increasing ED the value of LOO decreases, and the degree of the calculated PCE changes as well.…”
Section: Step C Uncertainty Propagationmentioning
confidence: 99%
“…For embankment and moraine-dammed lakes, there are two main approaches to computing dam failure: (i) numerical models based on mass and momentum balance equations supplemented by erosion laws (Begam et al, 2018;Castro-Orgaz & Hager, 2013;Faeh, 2007;Larocque et al, 2013), and (ii) conceptual models based on a series of differential equations accounting for the various processes at play (Capart, 2013;Peter et al, 2018;Walder & O'Connor, 1997). For ice-dammed lakes, the water's change phase should also be considered.…”
Section: Drainage and Dam Breakmentioning
confidence: 99%
“…Focusing the attention in dam engineering field, the most interesting examples aim to determine the model parameters for the risk assessment of earth fill dams [31,32,33,34].…”
Section: Interpretation Of the Dam Structural Behaviour From Monitorimentioning
confidence: 99%